2021
DOI: 10.1038/s41420-021-00789-2
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the tsRNA classification, function, and application in gynecological malignant tumors

Abstract: A large number of small non-coding RNAs derived from tRNAs, called tRNA-derived small RNA (tsRNAs), have been identified by high-throughput RNA sequencing of cell lines. Further research has revealed that they are not produced via random tRNA degradation, but through degradation by specific nuclease cleavages, such as Elac Ribonuclease Z 2 (ELAC2)/RNase Z, RNase L, Dicer, and angiogenin (ANG), the tsRNAs can be classified into the following types based on the location from which they have been derived from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 83 publications
0
25
0
Order By: Relevance
“…Nevertheless, the mechanism of tRNAs processing as well as the role of the involved RNases effectors should require further investigations. Anyway, many studies focused on tRFs functions recently received increasing attention, so that a more complete information and literature revisions are available [ 37 , 38 , 39 , 40 ].…”
Section: Trna-derived Small Interfering Rnasmentioning
confidence: 99%
“…Nevertheless, the mechanism of tRNAs processing as well as the role of the involved RNases effectors should require further investigations. Anyway, many studies focused on tRFs functions recently received increasing attention, so that a more complete information and literature revisions are available [ 37 , 38 , 39 , 40 ].…”
Section: Trna-derived Small Interfering Rnasmentioning
confidence: 99%
“…Transfer RNA (tRNA)-derived small RNAs (tsRNAs) are an emerging regulatory class of small noncoding RNA (ncRNA). Transfer halves (tiRNA) and tRNA-derived fragments (tRFs) are the two main categories of tsRNAs, 7 which are generated from mature or precursor tRNAs by multiple cleavage of tRNAs. 8 tsRNAs can be divided into several types rest with where they map on the precursor or mature tRNA transcript.…”
Section: Introductionmentioning
confidence: 99%
“…Based on tRFs’ mapped positions, tRFs are roughly divided into five types: tRF-5, tRF-3, tRF-2, tRF-1, and i-tRF. 7 Although the detailed function and mechanism of tsRNAs remain elusive, some paper has shown that tsRNAs play a key role in diabetes and diabetes-related diseases. For example, Yang et al found that altered tsRNAs may play vital roles in the pathogenesis of proliferative diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, tsRNAs were considered to be random degradation products of tRNAs thereby without attracting much attention. However, in recent years, numerous studies have indicated that tsRNAs occur in a specific biogenesis pattern and play a non-negligible role in the progression of various diseases, such as tumors ( Wen et al, 2021 ), reproductive-related diseases( Li et al, 2021 ), and cardiovascular diseases ( Cao, Cowan & Wang, 2020 ). Importantly, many studies have shown that cardiac pathological conditions can induce abnormal expression of tsRNAs in various cardiovascular diseases, such as rheumatoid heart disease with atrial fibrillation ( Yang et al, 2021 ), myocardial ischemia ( Liu et al, 2020 ), and atherosclerosis ( He et al, 2021 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%